Prevalence and risk factors for dysmenorrhoea among nursing student and its impact on their quality of life - Karanth, Shashikala; Liya, S. R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Dysmenorrhea is an important health problem of adolescent girls, that affects their quality of life and it is one of the leading causes of repeated school absenteeism. The purposes of this study was to determine the prevalence and risk factors for dysmenorrhea among nursing students and its impact on their quality of life. Methods: A prospective study was carried out in St Johns Nursing College, Bengaluru.200 nursing students aged between 18-20 years were included. Standardized questionnaires were used to obtain relevant data. Data was analysed using Chi-sq. test, correlation and regression analysis by SPSS version 23. Results: The prevalence of dysmenorrhea was 62.5%. The mean age, age at menarche and, the mean PABC of the students were 18.7±0.48, 13.3±1.20 and 74.96±16.14 respectively, which is not significant. The average length of menstrual cycle was between 28-30 days, duration of bleeding as 3-5 days. Duration of sleep, regular menstrual cycle and low BMI exhibited positive correlation (p<0.05) while Family history and exercising habits did not exhibit significant effect. Dysmenorrhea was significantly associated with repeated school absenteeism (16%). Conclusions: Dysmenorrhoea is found to be highly prevalent among nursing students and is one of the leading causes of absenteeism. Regular cycle, duration of sleep and low BMI were significant risk factors for dysmenorrhea. Findings of present study suggest the need for educating adolescent girls on appropriate and effective management of dysmenorrhea.